Droplet-based millifluidics as a new tool to investigate hydrate crystallization: Insights into the memory effect. (17th February 2015) - Martinez de Baños, Maria Lourdes; Carrier, Odile; Bouriat, Patrick; Broseta, Daniel
Abstract: A simple millifluidic method is used for studying hydrate crystallization. Regularly-spaced water drops of equal volume in the µl range separated by the guest (hydrate-former) phase are placed in transparent plastic tubing. Temperature and/or pressure are controlled. In one experiment several tens of water drops behaving as independent reactors are video-monitored for hydrate formation and melting events. This method is used here to gain insights into the 'memory effect'. The hydrate-former chosen is cyclopentane (CP), which forms hydrates at ambient pressure and temperatures below T eq =7.2 °C, the three-phase (CP, water, hydrate) equilibrium temperature. The statistics of hydrate nucleation events when chilling the water drops below T eq is observed to depend strongly on the thermal history, e.g., prior CP hydrate formation and subsequent melting at various prescribed temperatures (above 7.2 °C) and durations. When one or two of these parameters (melting temperature and duration) increase, the 'memory' of the hydrate previously formed fades: the subcoolings required for hydrate formation increase and are more scattered, i.e., they differ more from one drop to the other. The method also allows the visualization of single-drop events such as hydrate birth and growth. The results complement those obtained from more conventional methods and show the promises of using this method for investigating the kinetics of hydrate crystallization and melting. Graphical abstract: Highlights: Milli- & micro-fluidic tools are used to gain insights into hydrate crystallization. Upon hydrate melting, a guest-in-water emulsion forms that is fairly stable. The guest-in-water emulsion is unstable when the water is weakly salted. Droplet-based millifluidics permits the study of memory effects in hydrate formation.